DESIGN AND MANUFACTURE OF A ONE CAVITY MOULD FOR CASTING PISTON - OMORODION, I.; AMIEBENOMO, S.O (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paper, we design and manufacture a one cavity mould for the casting of a piston by sorting materials locally. The mould was also fabricated after the design calculations using basic machine tools likelathe, milling and drilling machines. Test conducted on the mould reveals sound casting with littleor no defects